Perception of Dialect Origin in Media Language: Is the Standard Language in Use a Supradialectal Idiom? - Čopa, Miljana B.; Miloradović, Sofija R. (Collection of Papers of the Faculty of Philosophy in Priština, 2024)
Based on the assumption that the standard language in use, including prosodic features, is a distinct supradialectal idiom that lacks regionally distinctive features and can be acquired by speakers originating from dialect regions that are structurally distant from the dialects that serve as the basis for the standard language, we aim to investigate whether speakers from different dialect regions can be identified in TV speech by their dialectal origin. The study involved 45 participants, including 30 high school students and 15 linguists, who were asked to identify the dialect origins of speakers from different dialect regions using a multimedia survey. The results of the study indicate that a person’s speech does not always clearly reveal their dialect base. Furthermore, the standard language can also be acquired by speakers of Serbian who come from dialect regions that are distant from the dialects that formed the basis of the standard Serbian language. This study could pave the way for further research in the field of perceptual dialectology and contribute to a broader and deeper understanding of this phenomenon.
Keywords: standard Serbian language; standard language in use; dialect origin; accent; unaccented quantity